Pengaruh Technostress Creator terhadap End-User Satisfaction dan End-User Performance Melalui Self Eficacy Sebagai Variabel Moderating - Sudirman Sudirman (Al-Buhuts, 2024)
This study aims to examine the effect of Technostress Creator on End-User Satisfaction and End-User Performance Through Self Efficacy as a Moderating Variable. This study uses a confirmatory approach, namely confirming the relationship or influence of the independent variable on the dependent variable. The data used is primary data obtained through questionnaires distributed to 55 respondents. The data were processed using statistical tools using multiple linear regression analysis models with the help of SPSS version 26. The results of the study found that: 1) Technostress Creator has a negative and significant effect on End-User Satisfaction; 2) Technostress Creator has a negative and significant effect on End-User Performance; 3) Self Efficacy can moderate the effect of Technostress Creator on End-User Satisfaction; 4) Self Efficacy cannot moderate the effect of Technostress Creator on End-User Satisfaction.